Импактот на радијалниот артериски пристап врз интервенцијата при акутен миокарден инфаркт - Калпак, Оливер (Медицински факултет, УКИМ, Скопје, 2018)
Introduction: Percutaneous coronary intervention (PCI) for ST-elevated Myocardial Infarction (STEMI) constantly evolves in methods in modalities progressively improving outcomes. The latest proposal for progress is a subtle change in arterial access from femoral to radial as the primary choice in STEMI patients. In recent years, our Cath lab underwent a meaningful change towards hundred percent radial approach in STEMI patients, making our Centre one of the only few on a global scale. Drawing from the specifics and accomplishments from the interventional cardiology Register came to the idea to investigate the outcomes in transfemoral vs. trans-radial PCI in STEMI patients. Aims: We sought to answer the question of whether an elegant change in the arterial access in PCI intervention can ultimately lead to more lives saved. Methods: This is a registry-based single-center longitudinal study conducted in the University Cardiology Clinic – Skopje, based on data from 5419 consecutive PCI in STEMI patients included in the Registry during the period of 2007 to 2015. We compared outcomes from 1371 in the transfemoral - TFA group and 4048 patients transradial - TRA access strategy. The all-comers study sample consists of PCI STEMI divided solely on different access strategy use. Primary points of research are access-related major bleeding, major cardiovascular events and mortality in 30 days and 1 year follow up time points. Furthermore, in our data analysis, we introduced Propensity Score Matching comparing both groups before and after the congruent pairs scoring in addition to plotting Kaplan Meier cumulative risk survival curves. Results: The groups were congruent in terms of baseline characteristics, risks and the achieved success of mechanical reperfusion. However, we found a tenfold difference in favor of the TRA group in the reduction of access-related major bleeding, 28 (0.7%) in TRA vs. 99 (7.2%) in TFA (OR 0.11 (95% CI 0.03-0.41 p <0.001). To put things in perspective, these results mean that by transitioning to the radial approach in PCI STEMI patients we prevented one case of severe bleeding in every 15 patients. In other words, we save 6 severe accessrelated bleeding complications for every 100 PCI STEMI patients. The difference of the TRA group benefit is formed in the 30 days of follow-up. The radial strategy has an impact in every 15 patients to prevent a serious, life-threatening hemorrhage. The use of the radial approach as the primacy access strategy results in one life saved in every 22 PCI STEMI patients. Conclusion: The complete change of access strategy towards the radial approach had a favorable impact on the overall PCI STEMI outcomes. In this study, we quantify and reflect the current improved results of the treatment for acute myocardial infarction at the University Clinic of Cardiology in Skopje. The elegant change to the radial artery during intervention significantly reduces the total hospitalization time, cost of treatment, rates of major accessrelated bleeding, mortality and major cardiovascular events.
The impact of radial access strategy on outcomes from acute myocardial infarction intervention
Докторска дисертација одбранета во 2018 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Дончо Донев.